Correction of Hypothyroidism Seems to Have No Effect on Body Fat - Okan Bakiner; Emre Bozkirli; Emine Duygu Ersozlu Bozkirli; Kursat Ozsahin (International Journal of Endocrinology)
Aim. We aimed to observe the effects of L-thyroxine replacement therapy on body fat content determined with various anthropometric methods and a bioelectrical impedance analysis method in patients with hypothyroidism. Methods. Forty-two women with naive autoimmune hypothyroidism were included. Also, 40 healthy participants were enrolled as a control group. Weight, body mass index, waist circumference, and subscapulary, suprailiac, femur, biceps, and triceps skin fold thicknesses were measured. Body fat percentages were calculated and body fat measurements were performed. Euthyroidism was maintained with L-thyroxine. At the 6th and 18th month, of therapy, measurements were reperformed. Results. Mean TSH levels were  mIU/L in hypothyroid group and  mIU/L in control subjects at admission. In hypothyroid patients, calculated body fat percentages were greater than those of the control subjects during follow-up. Body fat percentage of each hypothyroid case decreased at 6- and 18-month controls, but the decrements were statistically insignificant. Although skin fold thicknesses measured from all sites were observed to decline, only those obtained from femur and biceps showed a significant decrease ( and , resp.). Discussion. Correction of hypothyroidism did not cause any improvement in body weight and body fat percentage. The decrease in skin fold thicknesses might probably result from the reduction in subcutaneous mucopolysaccharide deposits.